Analysis of Transportation Department Supervision in Roadworthy Tests of Bus Vehicles in Mimika Regency - Piagi, Merlin; Raharusun o, Dionesia; Mote, Maria Fatima; Tabuni, Desi; Sandy, Stepanus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to find out how supervision is carried out byFacilities and Infrastructure Engineering and StandardizationvehicleBUS, Transportation Departmentin carrying out roadworthiness tests of BUS vehicles. This research uses qualitative descriptive data analysis techniques, and data collection techniques, interviews and observations according to the results obtained in the field. This research uses 4 public service management indicators proposed by Robert J Mocler and DR Gilbert Jr, namely standards, measurement, comparison, action. The problems faced regarding the roadworthiness test of BUS vehicles are, Standard Operating Procedures (SOP) which are not well socialized, inadequate network requirements and a lack of human resources regarding transportation testing. In this case, the inhibiting factor for the problem that occurs is the lack of socialization, budget and network requirements for periodic roadworthiness tests at the Transportation Service so that public awareness of carrying out regular tests is very low. From the research results, it can be concluded that the implementation of the roadworthiness test for BUS vehicles has gone well but is still not fully optimal, so regular monitoring needs to be carried out.